2019
DOI: 10.1080/19476337.2019.1596986
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and microstructural properties of wheat dough supplemented with Flammulina velutipes (mushroom) powder and soluble polysaccharides

Abstract: Partial substitution of wheat flour with Flammulina velutipes powder (FVP) or soluble polysaccharide (SPFV) at different addition levels, and the effects of which on the rheological and microstructural properties of dough were investigated. FVP significantly (P < 0.05) increased the water absorption but decreased the development time and stability of dough significantly (P < 0.05). Furthermore, it was capable of providing a weaker extension and harder dough with the increasing of FVP addition levels. FVP incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…The G' values of all samples were higher than that of G", indicating that the elastic properties of the doughs dominated their viscous properties (Khoigani et al, 2017), and all values of loss tangent tanδ were determined less than 1, indicating a typical dynamic rheological profile of weak gel with pronounced elastic properties (Ptaszek et al, 2009). G' and G" had a downward trend with the increasing GSP or GPP addition level compared to the control group, as shown in Figure 1(a,b,g,h), which was contrary to the results reported by Nie et al (2019) for wheat dough supplemented with Flammulina velutipes powder. The decrease of moduli might be attributed to different interactions between starch granules with different particle sizes of GSP (Moreira et al, 2014).…”
Section: Dynamic Rheological Properties Of Doughcontrasting
confidence: 79%
See 2 more Smart Citations
“…The G' values of all samples were higher than that of G", indicating that the elastic properties of the doughs dominated their viscous properties (Khoigani et al, 2017), and all values of loss tangent tanδ were determined less than 1, indicating a typical dynamic rheological profile of weak gel with pronounced elastic properties (Ptaszek et al, 2009). G' and G" had a downward trend with the increasing GSP or GPP addition level compared to the control group, as shown in Figure 1(a,b,g,h), which was contrary to the results reported by Nie et al (2019) for wheat dough supplemented with Flammulina velutipes powder. The decrease of moduli might be attributed to different interactions between starch granules with different particle sizes of GSP (Moreira et al, 2014).…”
Section: Dynamic Rheological Properties Of Doughcontrasting
confidence: 79%
“…This was probably due to the dietary fiber in grape powders, which could strengthen the WA ability of dough. The significantly increased water promoted swelling of wheat flour starch and proteins, and thus increase the viscosity of the dough (Nie et al, 2019). These results suggested that grape powders addition had weakened the gluten network structure of dough.…”
Section: Dynamic Rheological Properties Of Doughmentioning
confidence: 87%
See 1 more Smart Citation
“…The choice of mushroom objects was based on the best properties of these cultivable basidiomycetes. Winter mushroom Flammulina velutipes is a source of valuable nutritional food ingredients (Su et al, 2019;Nie et al, 2019), and it provides a natural basis for developing high-performance pharmaceuticals (Huang et al, 2019) and veterinary and medicinal preparations (Mahfuz et al, 2019;. The extremely important biologically active extracts and compounds from lacquered polypore Ganoderma lucidum exert pharmacological effects on tumour cells.…”
Section: Fungal-azospirillum Interactionsmentioning
confidence: 99%
“…Micrographs of instant noodles (gliadins were incorporated at the level of 3% and 5%) made from a variety DBW88 revealed the cavity-like structure increased and more hollow spaces were observed. Whereas on the addition of increasing glutenins from 3% to 5%, denseness in the network with an enhanced number of strands with the increase in the thickness was visible indicating a more bonded and compact structure Nie et al (2019). revealed the continuity and integrity of the gluten network comprising of gluten strands and gluten film binding the starch granules.…”
mentioning
confidence: 97%